IMPROVING MARINE CLAYS WITH ELECTROKINETICS METHOD - Daniel Tjandra; Paravita Sri Wulandari (Civil Engineering Dimension, 2007)
The high water content in marine clays could loosen the bond of soil particles, resulting in low bearing capacity and high compressibility of the soil. Excessive settlements could happened to the structures built on it. An electrokinetic process was attempted to reduce the high water content of the marine clay. An experimental study was conducted to evaluate the effect of electrokinetic on marine clay improvement. This study focused on the use of electrokinetic to enhance the soil bearing capacity of marine clay by improving index properties of the marine clay. The result of this research was obtained by doing several analyses on water content, pH value, and soil particles of soil sample located between cathode and anode. Based on the results from laboratory testing, it can be concluded that electrokinetic process decreased the water content and pH value of soil surrounding the anode. Also, soil particles surrounding the anode became in close proximity. This indicated that as it became closer to the anode, soil became denser.